PERAN CEMARA LAUT (Casuarina equisetifolia) DALAM PERBAIKAN IKLIM MIKRO LAHAN PANTAI BERPASIR DI KEBUMEN (The role of Casuarina equisetifolia on micro climate improvement of sandy beach land at Kebumen) - Beny Harjadi (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2017)
Sandy beach is a marginal land, when it is not managed properly the conditions will be worsened and at the end it cannot be planted. This marginal land is aggravated by unfavorable conditions such as extreme high temperatures, the presence of salt vapor that causes the plants to die, and the lacking of water for plants. With regard to this matter, it is necessary to conduct a research that aims to determine the role of Casuarina equisetifolia in improving the microclimate of sandy beaches. The research was conducted on sandy beaches in Karanggadung, Petanahan Subdistrict, Kebumen since 2005, with climate observations from 2009 to 2014. The climate observation method is by measuring light, air temperature, humidity, air pressure and altitude. Each measurement used three repetitions for each location and measured twice a day: 07.00 and 16.00. The results showed that the existence of C. equisetifolia gave a positive effect on micro climate improvement at Karanggadung Beach, Kebumen which included: 1) decreasing light intencity from 1925 lux to 213 lux, 2) decreasing air temperature from 31 °C to 25 °C, 3) increasing air humidity from 84% to 100%, 4) increasing air pressure from 1007 mb to 1008 mb, and 5) increasing sand dune level from 27 m ASL (Above Sea Level) to 35 m ASL.